2002
DOI: 10.1242/jcs.00049
|View full text |Cite
|
Sign up to set email alerts
|

Normal timing of oligodendrocyte development from genetically engineered,lineage-selectable mouse ES cells

Abstract: combinations of known signal molecules to promote the development of OPCs from selected, ES-cell-derived, neuroepithelial cells. We show that the earliest stages of oligodendrocyte development follow an ordered sequence that is remarkably similar to that observed in vivo, suggesting that the ES-cell-derived neuroepithelial cells follow a normal developmental pathway to produce oligodendrocytes. These engineered ES cells thus provide a powerful system to study both the mechanisms that direct CNS stem cells down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 73 publications
(114 reference statements)
2
86
0
Order By: Relevance
“…Because studies of nuclear organization rely on analysis at the single cell level, it was important to have a more homogenous population of cells, before and after differentiation. Therefore, we chose to use OS25 ES cells that allow for G418 selection of undifferentiated (Sox2 expressing) cells, and then selection against undifferentiated (Oct4 expressing) cells with Ganciclovir after differentiation (Billon et al 2002). The expression of alkaline phosphatase and SSEA-1 markers, and Oct4, confirmed the undifferentiated state of cells grown in the presence of LIF and G418 (Billon et al 2002;data not shown).…”
Section: Ra Induces a Temporal Program Of Hoxb Gene Expression In Es mentioning
confidence: 92%
See 2 more Smart Citations
“…Because studies of nuclear organization rely on analysis at the single cell level, it was important to have a more homogenous population of cells, before and after differentiation. Therefore, we chose to use OS25 ES cells that allow for G418 selection of undifferentiated (Sox2 expressing) cells, and then selection against undifferentiated (Oct4 expressing) cells with Ganciclovir after differentiation (Billon et al 2002). The expression of alkaline phosphatase and SSEA-1 markers, and Oct4, confirmed the undifferentiated state of cells grown in the presence of LIF and G418 (Billon et al 2002;data not shown).…”
Section: Ra Induces a Temporal Program Of Hoxb Gene Expression In Es mentioning
confidence: 92%
“…Undifferentiated OS25 ES cells were maintained on 0.1% gelatin-coated dishes in Glasgows' minimal Eagle medium containing 10% fetal calf serum, nonessential amino acids, 1 mM sodium pyruvate, 0.3 mg/ml L-glutamine, 0.1 mM 2-mercaptoethanol, 1000 U/mL human recombinant LIF, and 100 µg/mL G418 (Billon et al 2002).…”
Section: Es Cells Culture Differentiation and Tsa Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…To clarify the differences in their capacities to differentiate in vitro, rabbit pluripotent stem cells were induced to undergo further neural differentiation into oligodendrocytes. These are a more mature neural cell type than other neural cells such as neural stem cells, neurons, or astrocytes (32,33). Because the differentiation of pluripotent stem cells into oligodendrocytes was effectively induced by the addition of Noggin, further culture in the presence of Noggin was examined for 20 days (Fig.…”
Section: Rabbit Ips Cells Have a Limited Capacity To Differentiate Intomentioning
confidence: 99%
“…Embryonic stem (ES) cells are derived from the inner cell mass of blastocyst-stage embryos, and are pluripotent cells that are able to generate the entire repertoire of cell types in the body. Glial precursors with myelinogenic properties were derived from mouse ES cells [196][197][198]. Human ES cells [199,200] can be directed into neural fate [201,202].…”
Section: Embryonic Stem and Induced Pluripotential Cellsmentioning
confidence: 99%